The Regulatory Determinants of Economic Growth under Pandemic Challenges: Regional Cluster Issues and Patterns - Yurii Umantsiv; Pavlo Dziuba; Yuliya Yasko; Maryna Shtan; Halyna Umantsiv (Studia Regionalne i Lokalne)
The main objective of this paper is to discover the impact of the COVID-19 pandemic and regulatory conditions of doing business on economic growth of different economies, particularly in terms of the combined co-effect of the two mentioned factors. An econometric cluster model using the k-means method is developed. 172 economies were distributed between clusters based on three parameters: 1) rates of GDP growth for individual economies in 2020, as provided by the World Bank; 2) the World Bank Doing Business rating for 2020; and 3) the COVID-19 pandemic factor that is represented by the total accumulated number of cases officially fixed per 100,000 of population, as provided by the World Health Organization. The study proves that the COVID-19 pandemic appeared to be a substantial factor of economic growth for the vast majority of economies, which is reflected by the drop in their GDP even despite favourable conditions of doing business in some countries. Substantial compensating reciprocal influences are observed between the set of doing business factors and the COVID-19 pandemic factor.